Desempenho de sistema de tratamento e uso agrícola de água residuária sanitária no semiárido brasileiro - Araújo, Ana Beatriz Alves de (Universidade Federal Rural do Semi-Árido, 2021)
The need to move forward in the fields of sanitation and water resource management has resulted in recent reforms to legais frameworks and a significant increase in resources for sanitation. The high incidence of waterborne diseases in the Brazilian territory is attributed to the inadequacy of sanitary sewage systems, especially in the Brazilian semi-period. In this way, the urgent challenge of universal basic sanitation is posed. Given this scenario, the practice of water reuse allows better quality water resources to be used for more noble purposes. It must be taken into account that the reuse of water for agricultural purposes, carried out in a rigorous manner, can be an effective solution in the sustainability of water resources. For the treatment of sanitary wastewater there are several technologies, among them the septic tank together with the solar reactor, stand out for use in semi-arid regions due to the low relative cost of implantation and maintenance, in addition to the efficiency in removing contaminants that make it unfeasible. the use of sanitary wastewater for agricultural and forestry purposes. In view of the above, the present study aimed to monitor the removal of physical-chemical and microbiological attributes from sanitary wastewater through a treatment plant for agricultural purposes. Between the months of May of the year 2018 to April of the year 2019, 12 samples of the effluent were carried out; the collection of wastewater was made upstream of the septic tank and inside the solar reactor, after the exposure of the effluent for 12 h to ultraviolet radiation UVA and UVB. In the sanitary effluent, the following attributes were analyzed: biochemical oxygen demand, chemical oxygen demand, turbidity, total suspended solids, total solids, total coliforms, Escherichia coli, pH, CE, Ca2+, Mg2+, Na+, P, K+, CO32- , HCO3-, sodium adsorption ratio, Fe, Mn, Cu, Zn, Pb, Cd and Ni. The temperature and solar radiation were also monitored on the day of collection for the 12 h exposure of the effluent. All data were submitted to descriptive and multivariate analysis. And for the microbiological variables, total coliforms and Escherichia coli, a singular spectral analysis was developed, with prediction of the effluent behavior for the period of one year. The physical, chemical and microbiological quality of the treated effluent has been significantly improved with the use of the 12 h exposure time to solar radiation. All of the attributes analyzed in the study that were reduced were below the rates recommended by the environmental legislation in force in Brazil. The microbiological variable Escherichia coli had a reduction of 99.94%, after 12 hours of exposure to solar radiation, decreasing the equivalent to 4 logarithmic units, making possible unrestricted agricultural reuse according to the World Health Organization. This work becomes a pioneer in the use of singular spectral analysis to predict the behavior of sanitary effluent treated in the semiarid region, bringing the possibility of optimization of the analysis and time management processes. It is understood that this work requires a longer time series for the prediction of the outflow effluent to be carried out for the period of one year. The recommendation would be to develop a survey with a larger volume of samples
Keywords: Universalização do saneamento; Escassez hídrica; Legislação ambiental; Tanque Séptico; Desinfecção solar; Universalization of sanitation; Water scarcity; Environmental legislation; Septic tank; Solar disinfection; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO